Analysis of Working Capital Management in an Effort to Increase Liquidity and Profitability at PT Unilever Indonesia, Tbk - Imanuddin, Imanuddin; Monti, Renny; Taliding, Arianto (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to find out how working capital management and liquidity levels affect profitability at PT Unilever Indonesia, Tbk.The data used in this research is secondary data using a purposive sampling method, namely the financial position report (balance sheet), profit and loss report in the financial statements of PT. Unilever Indonesia, Tbk for the 2016-2023. The type of research is quantitative research because the data used is in the form of numbers which are then analyzed using multiple linear analysis. The results of this research were also tested using classical assumption tests and hypothesis tests. The research test results show that working capital and liquidity (current ratio) partially do not have a significant effect on profitability. Meanwhile, working capital and liquidity (current ratio) simultaneously have a significant influence on company profitability